Uma análise foucaultiana da corrida no ambiente hospitalar: disputa de saberes, poderes e produção de verdades - Tauana Wazir Mattar e Silva (2024)
The complexity of care has exceeded the knowledge of a single profession, overcoming a solely biological, medical-sanitary, and hygienist perspective on care practices. Initiatives promoting patient safety and healthcare quality demand coordination with a decentralized therapy. Therefore, there is a need for interdisciplinary communication mechanisms that enable collaborative and safe care. Bedside rounding is considered one of the forms of interdisciplinary dialogue to ensure the rapid flow of information linked to care. It is thus a space for professionals from different categories to collectively discuss and determine the conduct to be adopted. Although interdisciplinary practice enhances integration in healthcare work by articulating different knowledge and professional practices, in the hospital setting there are certain relationships typical of organizations, including the struggle for space and defense of interests that lead to a reflection on how social agents are inserted in a system of well-established positions and power relations. From the perspective of power relations, it is believed that the coordinated work between health teams presents itself as a weakness in guaranteeing that health behaviors are aligned. Aiming to analyze the configuration of bedside rounding from the power perspective of power relations formed in and by the knowledge of doctors and nurses in open and closed departments of a hospital, this study consists of qualitative research developed from a post-structuralist view based on Michael Foucault's theoretical-methodological framework. The chosen setting was the Intensive Care Unit and Station Four of an Inpatient Unit of a large philanthropic general hospital, located in Belo Horizonte, Minas Gerais, Brazil. Bedside rounding was observed in the departments, and interviews with a semi-structured script were carried out with 11 doctors, 18 nurses, and eight key informants (as they stood out during the bedside rounding observation in the departments). Through discourse analysis, three main empirical categories were identified: bedside rounding: elements and conditions; bedside rounding in the perception and subjectivation of the involved agents; and interdisciplinary collaboration in bedside rounding. The participants' speeches, associated with what was observed, portray the bedside rounding as a reflection of the relational environment. The results demonstrated that the bedside rounding structure doesn’t favor coordinating the work between doctors and nurses; it also hinders the circulation of power, damaging interdisciplinary initiatives and keeping doctors as the main agents in clinical decisions, compromising the comprehensiveness of care. The power relations involved in the bedside rounding process negatively interfere with the quality of interdisciplinarity in care practices between doctors and nurses in the hospital setting, affecting patient care. Studies of this nature might support reflections on individual and collective practices, considering that it is possible to establish greater fluidity in relationships between health teams towards increasingly modern and safe care.